Neurochemistry: Rapid Growth Cone Uptake and Dynein‐Mediated Axonal Retrograde Transport of Negatively Charged Nanoparticles in Neurons Is Dependent on Size and Cell Type (Small 2/2019). Issue 2 (11th January 2019) - Lesniak, Anna; Kilinc, Devrim; Blasiak, Agata; Galea, George; Simpson, Jeremy C.; Lee, Gil U.
Abstract : In article number1803758, Gil U. Lee and co‐workers present a novel microfluidics device which makes the study of nanoparticle uptake and transport in neuron cultures possible. The somatic chamber at the top of this fluorescence image shows somato‐dendritic nanoparticle (red) uptake in the primary cortical neurons. At the end of a 6 h incubation period, neurons with axons in the axonal chamber at the bottom of the image are labelled with Calcein (green) to distinguish them from neurons with axons in the somatic chamber.